Reduction Of Outrigger Wide To Maximize Fishing Boat Landing Area Capacity In Prigi Fishing Port - Sunardi, Sunardi; Amirruddinsyah, Muhammad Makki; Sulkhani, Eko; Yulianto, Ardi Nugroho (International Journal of Marine Engineering Innovation and Research, 2024)
Jukung fishing boats, prevalent in Prigi, face challenges due to their wide design (approximately 5 meters on both sides). This excessive width often necessitates berthing further from the coast. To address this issue, this study investigates the feasibility of reducing outrigger width to increase berthing capacity at PPN Prigi while ensuring vessel stability. Through a systematic analysis of various outrigger widths (1.5, 1.25, 1, and 0.75 meters), the study determined that a reduction to 1 meter maintains vessel stability as per HSC 2000 Annex 7 and Annex 749 (18) Ch3 design criteria. A 1-meter reduction in outrigger length can increase berthing efficiency by 66% for a standard 15-meter berth with 30-40 cm ship spacing. Consequently, the east dock of PPN Prigi can accommodate an additional 94 jukung vessels, raising the total capacity from 142 to 236. This research provides valuable insights for optimizing port infrastructure and enhancing the operational efficiency of the fishing community in Prigi.